1993
DOI: 10.1016/0014-5793(93)81460-h
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5‐trisphosphate releases Ca2+ from vacuolar membrane vesicles of Saccharomyces cerevisiae

Abstract: Inositol 1.4,5-trtsphosphate (IP,) induces a release of Cal' from vacuolar membrane vesicles of Succharomyces cerewiue. The amount released is dependent on IP, concentration (concentration for half maximal effect, K,,,, apparent = 0.4 PM). Myo-inositol, and mositol 1,Cbisphosphate up to 50 PM have no effect on Ca" levels in the vesicles. The IP,-induced Ca*' release is blocked by dantrolene and 8-(N,N-diethylamino)-octyl 3.4.5-trimethoxybenzoate-HCI (TMB-8). which are known to block Ca" release from Ca" stores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…The difference in inhibitor signatures indicates that the large conductance channel is localized in vacuoles as TMB-8, dantrolene and heparin are widely reported to inhibit the IP3-induced Ca 2+ release from vacuoles in S. cerevisiae [TMB-8 and dantrolene (Belde et al, 1993)], in N. crassa [dantrolene (Cornelius et al, 1989)], in red beet root [heparin and TMB-8 (Brosnan and Sanders, 1990;Alexandre et al, 1990)], and C. albicans [partial inhibition by heparin (Calvert and Sanders, 1995)]. The localization of the large conductance channel on step gradients confirms its origin as vacuolar.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in inhibitor signatures indicates that the large conductance channel is localized in vacuoles as TMB-8, dantrolene and heparin are widely reported to inhibit the IP3-induced Ca 2+ release from vacuoles in S. cerevisiae [TMB-8 and dantrolene (Belde et al, 1993)], in N. crassa [dantrolene (Cornelius et al, 1989)], in red beet root [heparin and TMB-8 (Brosnan and Sanders, 1990;Alexandre et al, 1990)], and C. albicans [partial inhibition by heparin (Calvert and Sanders, 1995)]. The localization of the large conductance channel on step gradients confirms its origin as vacuolar.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that Ca 2ϩ mobilization through IP 3 receptors is required for nuclear fusion (41), in vitro liposome fusion (11), and the fusion of secretory granules with the plasma membrane (18). Moreover, Ca 2ϩ is stored in the vacuole and IP 3 has previously been shown to stimulate its release (4). Third, the products of phospholipase D and phospholipase C may create a membrane section that is physically capable of undergoing membrane fusion by changing the phospholipid composition (18,38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inositol trisphosphate (IP 3 ) releases vacuolar Ca 2ϩ through an as yet unknown channel (26). Additionally, mTRP3 is activated by IP 3 by direct interaction with the IP 3 receptor (27).…”
Section: Resultsmentioning
confidence: 99%